Vaccination coverage and factors associated with routine childhood vaccination uptake in rural Vellore, southern India, 2017. Issue 23 (21st May 2019) - Francis, Mark Rohit; Nuorti, J. Pekka; Kompithra, Rajeev Zachariah; Larson, Heidi; Balraj, Vinohar; Kang, Gagandeep; Mohan, Venkata Raghava
Highlights: The coverage of individual antigens (>90%) and full vaccination (84%) were high. Only 71% of children received the vaccines according to the recommended schedule. We found no socio-demographic disparities in vaccination uptake in this population. Parent familiarity with schedule was associated with vaccination coverage. Targeting interventions at pregnant women may improve awareness of the schedule. Abstract: Background: Vellore district in southern India was selected for intensified immunization efforts through India's Mission Indradhanush campaign based on 74% coverage in the National Family Health Survey in 2015. As rural households rely almost entirely on the Universal Immunization Program (UIP), we assessed routine immunization coverage and factors associated with vaccination status of children in rural Vellore. Methods: We conducted a cross-sectional household survey among parents or primary caretakers of children aged 12–23 months during August–September 2017 using two-stage, EPI cluster sampling. We verified vaccination histories from vaccination cards and collected data on sociodemographic and non-socio-demographic characteristics by using mobile data capture. Associations with vaccination status were examined with univariate and multivariate logistic regression models. Results: A total of 643 children were included. Coverage of BCG, third dose pentavalent/DPT, measles/MR vaccines and full vaccination (BCG, three doses of polio and pentavalent/DPT and measles/MR vaccines) among children with vaccination cards (n = 606) was 94%, 96%, 93% and 84%, respectively. Of children with vaccination cards, 70.8% had received all recommended doses according to the UIP schedule. No socio-demographic differences were identified, but parents' familiarity with the schedule (Adjusted Prevalence Odds Ratio (aPOR): 2.06, 95%CI = 1.26–3.38) and receiving information on recommended vaccinations during antenatal visits (aPOR: 2.16, 95% CI = 1.13–4.12) were significantly associated with full vaccination status of the children. Conclusions: We found higher UIP antigen coverage and proportion of fully vaccinated children than previously reported from rural Vellore. However, adherence to the recommended schedule was still not optimal. Our study highlights the potential of improving parental awareness of vaccination schedule and targeting health education interventions at pregnant women during antenatal visits to sustain and improve routine immunization coverage.